Sequence variants of human papillomavirus type 16 in clinical samples permit verification and extension of epidemiological studies and construction of a phylogenetic tree. - Ho, L (1991)
Genomic variability between different viral isolates provides a powerful epidemiological tool for verifying ultrasensitive diagnostic procedures, understanding infectious pathways in individuals and human populations, and studying viral evolution. The potential of this approach has not yet been exploited for the diagnosis of human papillomaviruses (HPVs) like HPV type 16 (HPV-16), which are involved in genital cancer. Toward this end, we amplified by polymerase chain reaction, cloned, and sequenced a 364-bp noncoding segment of the HPV-16 genome from cell lines, cervical biopsy specimens, and cervical smears. The HPV-16 genomes in the cell lines SiHa and CaSki showed an identical point mutation, and in the SiHa cell line it had an additional 38-bp deletion. Only 4 of 22 cervical lesions biopsied from patients at several hospitals in Singapore contained HPV-16 DNA with the prototype sequence, while the DNAs of the other 18 cervical lesions differed by 1 to 10 mutations. This excludes contaminations with cloned HPV-16 DNA as the source of this DNA. To test whether this diversity was a geographic idiosyncrasy, we analyzed 25 cervical biopsy specimens from Brazil. Eight of these contained the prototype sequence, while 17 were mutated. Altogether, 11 genomic variants were found in the Singaporean samples and 12 genomic variants were found in the Brazilian samples, and only 5 of these occurred identically in both cohorts. All variants could be connected to form a phylogenetic tree, with some branches being specific for each cohort. This suggests that the variants did not originate over a short period in the individual patient but, rather, evolved consecutively while spreading throughout humankind.(ABSTRACT TRUNCATED AT 250 WORDS)